Problematika Pembelajaran Berbasis Online pada Lembaga Pendidikan Nonformal Era Pandemi Covid-19 (Studi Kasus di Madrasah Diniyah Manbaul Huda) - Farha, Asfiya; Khusnah, Nailal; Nugroho, Puspo (Fitrah: Journal of Islamic Education, 2020)
Implementation of education in the Covid-19 era still has to pay attention to the needs of children, including in formal educational institutions such as madrasah diniyah. Of course the learning that is carried out is in the corridor of health protocols and the use of online or online systems. Obstacles and obstacles are certainly the minus side of online system learning. This paper seeks to examine in detail the problems of online-based learning in non-formal educational institutions. The focus of the discussion is aimed at the problematic aspects and efforts to solve them at Madrasah Diniyah Manbaul Huda. This research uses a descriptive qualitative approach, with interview techniques. Furthermore, the data were analyzed using data reduction techniques, data display and drawing conclusions. The results of this study indicate that (1) the internet network, the cost of internet data packages, and the limited number of family smartphones are the problems of learning the online system at Madrasah Diniyah Manbaul Huda; (2) Some of the efforts that the teacher can make are preparing online learning, preparing a new schedule and socializing that the teaching and learning process will be through online learning.